Inclusion of Fly Ash Effects in adm1 Calibration and Validation of a Simple Function Using Real Wastewater - Lauzurique-Guerra, y (Springer Science and Business Media B.V., 2025)
Including a source of trace elements such as fly ash (FA) in the ADM1 has yet to be addressed, including calibration and validation. The present work aimed to propose, calibrate, and validate a simple function for including the FA effect in the ADM1 using real wastewater from the winery industry. The new function and the ADM1 were calibrated with data of daily methane production coming from a biochemical methane potential (BMP) test of winery wastewater without FA and validated for BMPs using five FA concentrations (25, 50, 75, 100, and 150 mg/L). The ADM1 calibration showed that the model fits well with the experimental data, although the parameter values are lower than the range reported in the literature. The calibration of the proposed function fits well with the experimental data under all conditions, including the inhibition and stimulating zones. Lastly, the modified ADM1 could accurately represent the accumulated methane at different FA concentrations, with NRMSE between 0.0635 and 0.1342. Furthermore, the sensitivity analysis shows that the proposed function only requires calibrating one parameter (ki). Thus, the proposed model is robust and valid for all the tested conditions. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.